2009
DOI: 10.1111/j.1365-2095.2008.00602.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid nutritional quality of sea urchinParacentrotus lividus(Lamarck 1816) eggs and endotrophic larvae: relevance for feeding of marine larval fish

Abstract: PortugalSea urchin eggs and larvae have been suggested as potential live prey for marine fish larval feeding. This study evaluated the fatty acid composition of Paracentrotus lividus eggs, prisms and four-armed plutei, obtained from wild and captive broodstocks fed on raw diets: maize, seaweed and a combination of maize and seaweed. Amounts of essential fatty acids (EFA) for marine fish larvae [arachidonic acid (ARA), eicosapentaenoic acid (EPA) and docosahexanoic acid (DHA)] were determined in eggs and endotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 43 publications
6
31
1
Order By: Relevance
“…As already suggested by Gago et al (2009), we confirmed that FA profiles of sea urchin eggs and embryos can be controlled through broodstock nutrition. This could play a role in the development of new feeds and protocols for first feeding of sea urchin larvae.…”
Section: Accepted M Manuscriptsupporting
confidence: 88%
See 1 more Smart Citation
“…As already suggested by Gago et al (2009), we confirmed that FA profiles of sea urchin eggs and embryos can be controlled through broodstock nutrition. This could play a role in the development of new feeds and protocols for first feeding of sea urchin larvae.…”
Section: Accepted M Manuscriptsupporting
confidence: 88%
“…Fatty acid composition of gonads, eggs or larvae have been described in several echinoid species such as Paracentrotus lividus, Psammechinus miliaris, Strongylocentrotus droebachiensis, Dendraster excentricus and Lythechinus variegatus (Cook et al, 2000;George et al, 2000;Castell et al, 2004;Hughes et al, 2006;Schiopu et al, 2006;Gago et al, 2009;Suckling et al, 2011;Carboni et al, 2012). It is generally recognized that FA compositions of sea urchin gonads reflect dietary inputs although reproductive status could alter relative FA abundance in P. lividus (Hughes et al, 2005, Martinez-Pita et al, 2010.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Our data on fatty acid profile of the early development stages differ from that reported by Gago et al, (2009). However, the only likely comparable treatment used in that study was the "wild" diet but, unfortunately, details of that diet were not reported.…”
Section: Larval Development and Fatty Acid Compositioncontrasting
confidence: 55%
“…Captive sea urchins were cultivated for 5 months on a recirculation seawater rearing system with similar physical conditions (35 g L -1 salinity; 18 ± 0.5°C temperature; 14L:10D photoperiod and 700 lux overhead illumination) as described by Luis et al (2005) and Gago et al (2009). A mix diet of yellow grains of maize Zea mays, with fragments of the commercial dried seaweed Laminaria ochroleuca (Kombu) was given alternatively two times per week to these captive sea urchins.…”
Section: Methodsmentioning
confidence: 99%
“…Emergent P. lividus culture requires a continuous supply of eggs and larvae (Grosjean et al 1998, Cook andKelly 2007); mass production of P. lividus eggs and larvae for marine fish larvae feeding is an hypothesis recently proposed (Luis et al 2005, Gago et al 2009) in spite of first results showing a lower ability than Brachionus spp. (Gago et al 2010); and at a small scale, P. lividus eggs and larvae are also needed as biological tools for different studies such as in embryological and toxicological research (e.g.…”
Section: Introductionmentioning
confidence: 96%